Analytical bootstrap methods for censored data. Issue 2 (2002) - Hutson, Alan D.
Abstract : Analytic bootstrap estimators for the moments of survival quantities are derived. By using these expressions recommendations can be made as to the appropriateness of bootstrap estimation under censored data conditions.